A contribuição de aulas práticas apoiadas na aprendizagem colaborativa para o processo de ensino-aprendizagem de biologia - Fidelis, Gisele Aparecida (2017)
The teachers' concern with the effectiveness of Biology teaching is permeated by the wide range of contents present in the curriculum, together with the difficulty in systematizing them mainly by the working conditions. It is the role of the teacher to elaborate the teaching work plan according to your school reality and to establish teaching strategies that allow learning. In this context, the practical class is a didactic modality that allows greater interaction between the students and according to Vygotsky's Sociocultural Theory, the interaction allows the exchange of knowledge and the consequent learning. The objective of this research was to investigate if the practical classes supported in Collaborative Learning can contribute to the teaching-learning process of Biology subjects. The present research adopted the qualitative methodology and the theoretical assumptions of Collaborative Learning. The instruments for the constitution of the data were semi-structured interviews, questionnaires, observation and application of a didactic unit according to the stages of Collaborative Learning and adapted for this study. The intervention took place in a school in the city of Maringá, PR, with 38 high school students and the respective biology teacher totaling 39 participants. The data were treated by the Content Analysis method and the categories of analysis defined according to the investigations carried out. For the teacher perception, the categories were listed working conditions and teaching strategies; for student perception, the importance of practical classes, content addressed and teaching strategies; and for the didactic intervention using the stages of Collaborative Learning, the categories: student participation, interaction and contribution to teaching-learning. The results show that the teacher's perception evidenced the difficulties faced in the present time, among them the low hours of the discipline, the lack of a laboratory technician of Sciences and Biology and the precarious school infrastructure. In the investigation of student perception, the data obtained reveal that students recognize the importance of practical classes for learning and that differentiated activities arouse interest in learning. Throughout the didactic intervention it is possible to perceive the wide participation of the students in front of the mediation of the researcher. This research provided the studentstudent and teacher-student interaction and contributed to the effectiveness of the teachinglearning process of Biology.